Land evaluation for development ([ Rome ], 1976)
This book provide information about how land is evaluated, the basic methodology for land evaluation.
Đánh giá và quy hoạch sử dụng đất ứng dụng
Keywords: Land use, rural,Soil science,Soil surveys,Sử dụng đất nông thôn,Khoa học đất,Khảo sát đất